Broadening of microwave heating beams in the DIII-D tokamak by edge turbulence. (1st April 2023) - Brookman, M.W.; Holland, L.A.; Thomas, M.B.; Austin, M.E.; Barada, K.; Gentle, K.W.; La Haye, R.J.; Leddy, J.B.; Petty, C.C.; Rhodes, T.L.; Yan, Z.; Vann, R.G.L.; et al.
Abstract: We have demonstrated for the first time that turbulent plasma density fluctuations in the edge of the DIII-D tokamak are responsible for substantial broadening of an injected microwave beam by successful quantitative comparison between experimental observations and first principles 2D full-wave simulations. The broadening of the beam has important implications for control of tokamak discharges through localized electron cyclotron deposition needed for eliminating magnetohydrodynamic instabilities. This new predictive capability is mandatory to design & operate present & future tokamaks in such a way that microwave heating schemes achieve their intended objectives.